Upaya Peningkatan Literasi Digital Masyarakat Desa Tanjung Medan - Budianto Bangun; Mulkan Ritonga; Rahma Muti’ah; Syahrol Sulaiman (STMIK Royal, 2022)
Through digital literacy in order to improve knowledge, by carrying out community service, it plays an important role with training on efforts to improve community digital literacy which was carried out in Tanjung Medan village, with participants who were followed by the community and Tanjung Medan village officials. raised the title of service, namely